Jane Addams : champion of democracy - Fradin, Judith Bloom (Clarion Books, 2006)
Presents a biography of Jane Addams, suffragist, civil rights activist, and founder of Hull House in the slums of Chicago that draws from hundreds of historical documents; and contains archival photographs of her life and activities.